Prophetic Food Program: Integrating Islamic Values and Local Food Literacy to Develop Moral Character in Elementary Students - Nuraly Masum Aprily; Nana Supriatna; Mubiar Agustin; Ernawulan Syaodih (Jurnal Pendidikan Indonesia, 2026)
The low level of local food literacy and the weak development of moral character among elementary school students remain critical problems due to the dominance of instant food consumption and the limited integration of value-based education. These conditions negatively affect students’ nutritional awareness, hygiene, justice, and ethical eating behavior. This study aimed to develop and examine the effectiveness of the Prophetic Food Program in enhancing students’ local food literacy and moral character. A mixed-methods approach with a sequential exploratory design was employed. The research subjects consisted of 70 fifth-grade students as experimental participants, as well as 140 students and 14 teachers as perception survey respondents. Data were collected through tests, questionnaires, observations, interviews, and documentation. Data analysis applied qualitative thematic analysis and quantitative paired t-test and N-Gain analysis. The findings indicate that the program significantly improves students’ knowledge, attitudes, and practices toward local food as well as the internalization of prophetic values (al-‘adl, al-ṭahārah, al-qanā'ah, al-karīm, and al-akhlāq al-karīmah) with a high effectiveness category. This study implies the importance of integrating Islamic value-based character education with local food literacy in elementary schools.